2020
DOI: 10.3390/molecules25040853
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Chemical Diversity of Marine Sponge-Derived Microorganisms over the Last Two Decades from 1998 to 2017

Abstract: Marine sponges are well known as rich sources of biologically natural products. Growing evidence indicates that sponges harbor a wealth of microorganisms in their bodies, which are likely to be the true producers of bioactive secondary metabolites. In order to promote the study of natural product chemistry and explore the relationship between microorganisms and their sponge hosts, in this review, we give a comprehensive overview of the structures, sources, and activities of the 774 new marine natural products … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 262 publications
(354 reference statements)
0
33
0
1
Order By: Relevance
“…Marine sponges (phylum Porifera) are among the oldest Metazoans on Earth ( Webster and Taylor, 2012 ). Due to their marine benthic environment and highly efficient filter-feeding abilities, sponges harbor abundant microorganisms, including bacteria, fungi, archaea, and microalgae ( Cheng et al, 2020 ). In fact, our previous studies identified 363 strains from 49 sponge species, including 92 actinobacterial isolates with diverse antibacterial potential, in which most streptomycetes displayed moderate to strong antibacterial activity by using the minimal medium that inhibited several Gram-positive and -negative indicators ( Liu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Marine sponges (phylum Porifera) are among the oldest Metazoans on Earth ( Webster and Taylor, 2012 ). Due to their marine benthic environment and highly efficient filter-feeding abilities, sponges harbor abundant microorganisms, including bacteria, fungi, archaea, and microalgae ( Cheng et al, 2020 ). In fact, our previous studies identified 363 strains from 49 sponge species, including 92 actinobacterial isolates with diverse antibacterial potential, in which most streptomycetes displayed moderate to strong antibacterial activity by using the minimal medium that inhibited several Gram-positive and -negative indicators ( Liu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Rédou et al (2015) provided evidence that almost all fungal isolates in their study (96% of the 200 filamentous fungi and yeasts) had at least one gene involved in a secondary metabolite biosynthesis pathway [ 19 ], for example genes that encode enzymes involved in polyketides production (Polyketide Synthase, PKS), terpenoids (Terpene synthases, TPS) or non-ribosomal peptides (Non-Ribosomal Peptide Synthetase, NRPS). Along with this study, several studies have demonstrated antimicrobial activities of diverse marine fungi [ 20 ], deep-subseafloor fungi [ 21 ], and antimicrobial, antitumoral and antioxidant activities of sponge-associated marine fungi [ 22 ].…”
Section: Introductionmentioning
confidence: 91%
“…One of the features of marine natural sources is that they can act as a continuous source of bioactive molecules [ 88 ]. Two major sources of marine-derived natural products are marine organisms and fungi [ 104 ]. Investigations showed that the production of these metabolites is not a random phenomenon and is related to the ecological niche [ 105 ].…”
Section: Marine-derived Natural Products and Associated Sourcesmentioning
confidence: 99%
“…Investigations showed that the production of these metabolites is not a random phenomenon and is related to the ecological niche [ 105 ]. According to this fact, chemists who working on marine natural products, are trying to discover new species which produce these metabolites [ 104 ] through unique metabolic and genetic pathways [ 88 ]. So, the marine organisms and fungi absorbed a lot of attention [ 106 ].…”
Section: Marine-derived Natural Products and Associated Sourcesmentioning
confidence: 99%